Evaluation of Distributive Frequency of Oral Contraceptive Pills Consumption in Women with Cerebrovascular Events Admitted in Farshchian Hospital of Hamadan between 1997-2007 - Mehrdokht Mazdeh (Journal of Fasa University of Medical Sciences, 2011)
Background & Objectives: Although there is no prolonged time elapsed from propagation of oral contraceptive pills (OCP), case reports demonstrated occurrence of pulmonary embolism and cerebral infarction in women using these pills. Present study was done to specify distributive frequency of oral contraceptive pills consumption in women with cerebrovascular events admitted in Farshchian hospital of Hamadan between 1997 to 2007. Materials & Methods: Every woman with cerebrovascular events during years 1997-2007 who was admitted in Farshchian hospital of Hamadan and her dossier was present in archive of hospital, were carefully checked and those who hadn’t exclusion criteria, were include in this study, a total of 1587 of them with respect to their Characteristics such as type of cerebrovascular event, age, type of oral contraceptive pill and duration of pill use were extracted from patient dossier and registered in respective checklist. Results: 24.1% of patient used oral contraceptive pill and 76.9% of patients were non users. Mean age of OCP users and non users were 45 years. Mean duration of pill use among these patients was 33 months. In assessing type of vascular events, in the group OCP users 73.1% and non users 66.4% had ischemic stroke.Which was statistically significant. In the group OCP users 24.6% and non users 29.1% were hemorrhagic stroke.. Also in the group OCP users 2.3% and non users 4.5% were affected sagital sinuses thrombosis that showed no significant difference. Among OCP users 85% of the patients used OCP, LD and 15% of the patients OCP, HD. Conclusion: The present study showed, the ischemic stroke rate of the patients with OCP consumption were significantly more than those of non users.